Suporte de Sistema Operacional para Redes de Sensores - Wanner, Lucas Francisco; Fröhlich, Antônio Augusto (Anais do Workshop de Sistemas Operacionais (WSO); 2008: Anais do V Workshop de Sistemas Operacionais, 2008)
Several research projects have aimed at solving the problem of system support for sensor networks. However, most of them either fail in correctly dealing with sensor network application requirements, or present prohibitive overhead. This work presents the project and implementation of a runtime support environment for wireless sensor network applications based on the EPOS operating system. This environment provides applications with hardware support, configurable communication, power management, and a data acquisition system, and presents significant advantages when compared to other sensor network operating systems.